2020
DOI: 10.1186/s43042-020-00063-7
|View full text |Cite
|
Sign up to set email alerts
|

The associations among RARRES2 rs17173608 gene polymorphism, serum chemerin, and non-traditional lipid profile in patients with metabolic syndrome

Abstract: Background The adipokine chemerin retinoic acid receptor responder protein 2 (RARRES2) has been associated with insulin resistance, type II diabetes mellitus (T2DM), obesity, and metabolic syndrome (MetS). The impact of RARRES2 rs17173608 gene polymorphism on MetS and chemerin levels is not completely elucidated. This study included 100 patients with MetS and 68 healthy subjects (non-MetS group). The RARRES2 rs17173608 gene variant was analyzed by tetra amplification refractory mutation system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Chemerin expression and secretion are reported to increase significantly with adipogenesis. A previous study showed a significant relation between LDL and GG chemerin genotype among adults with metabolic syndrome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemerin expression and secretion are reported to increase significantly with adipogenesis. A previous study showed a significant relation between LDL and GG chemerin genotype among adults with metabolic syndrome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We only included patients that had stable CAD with more than 50% stenosis. We excluded obese patients as obesity may influence the outcome of the study, as rs17173608 had been associated with obesity in previous studies [ 4 , 15 ]. Thus, the sample size is smaller.…”
Section: Methodsmentioning
confidence: 99%
“…Chemerin induces angiogenesis of endothelial cells and results in endothelial dysfunction [ 3 ]. Besides which, it can activate inflammatory response and oxidative stress in adipose tissue, results in insulin resistance and further enhance endothelial dysfunction [ 4 ]. Endothelial dysfunction and insulin resistance cause the progression of type 2 diabetes (T2D) and atherosclerotic coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations